Japan and the West : The Filled Void - Addiss, Stephen; Brüderlin, Markus; Epprecht, Katharina; Kawamura, Kazuhisa; Lütgens, Annelie; Muschg, Adolf; Okuda, Osamu; Osaki, Shinichiro; Schneider, Ulrich; Speidel, Manfred; Taut, Bruno; Kunstmuseum Wolfsburg, Wolfsburg (Wolfsburg : Kunstmuseum Wolfsburg, 2007)
Andre, Carl ; Beuys, Joseph ; Bissier, Julius ; Byars, James Lee ; Cage, John ; Federle, Helmut ; Fox, Terry ; Geiger, Rupprecht ; Giacometti, Alberto ; Horn, Roni ; Itten, Johannes ; Judd, Donald ; Kaiser, Raffi ; Klee, Paul ; Klein, Yves ; Laib, Wolfgang ; Long, Richard ; Marioni, Joseph ; Martin, Agnes ; Merz, Gerhard ; Newman, Barnett ; Niedermayr, Walter ; Palermo, Blinky ; Reinhardt, Ad ; Rockenschaub, Gerwald ; Rückriem, Ulrich ; Ruthenbeck, Reiner ; Ryman, Robert ; SANAA ; Sandback, Fred ; Suda, Yoshihiro ; Tuttle, Richard ; Twombly, Cy ; Yu-ichi
Japan and the West : The Filled Void, Kunstmuseum Wolfsburg, Wolfsburg, 2007-09-22. 2008-01-13
boek
Keywords: Japan